2015
DOI: 10.1097/ico.0000000000000381
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Nerve Structure and Function After Long-Term Wear of Fluid-Filled Scleral Lens

Abstract: Purpose To determine if long-term wear of a fluid-filled scleral lens alters basal tear production, corneal sensation, corneal nerve density and corneal nerve morphology in two disease categories. Methods Patients recruited from the Prosthetic Replacement of the Ocular Surface Ecosystem (PROSE) treatment program at Weill Cornell Medical College were categorized into two groups: distorted corneas (DC) or ocular surface disease (OSD). We measured tear production, central corneal sensation, sub-basal nerve dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…Another report assessed basal tear production, corneal sensation, corneal nerve density, and corneal nerve morphology after long-term wear of SLs in two groups, with distorted corneas (DC) and ocular surface disease (OSD) including primary dry eye syndrome, Sjögren's syndrome, ocular graft-versus-host-disease, post-refractive surgery dry eye syndrome, dry eye syndrome associated with blepharitis, and exposure keratopathy. 38 Significant changes in the lacrimal functional unit were found only in patients with DC probably because of the difference in disease pathophysiology between corneal irregularity and OSD. Furthermore, corneal sensation was increased only in the DC group.…”
Section: The Impact Of Sls On the Ocular Surface In Sjögren's Syndromementioning
confidence: 99%
“…Another report assessed basal tear production, corneal sensation, corneal nerve density, and corneal nerve morphology after long-term wear of SLs in two groups, with distorted corneas (DC) and ocular surface disease (OSD) including primary dry eye syndrome, Sjögren's syndrome, ocular graft-versus-host-disease, post-refractive surgery dry eye syndrome, dry eye syndrome associated with blepharitis, and exposure keratopathy. 38 Significant changes in the lacrimal functional unit were found only in patients with DC probably because of the difference in disease pathophysiology between corneal irregularity and OSD. Furthermore, corneal sensation was increased only in the DC group.…”
Section: The Impact Of Sls On the Ocular Surface In Sjögren's Syndromementioning
confidence: 99%
“…Consistent with these reports of broad utility, a survey of 292 practitioners revealed that scleral lens wear improves vision and reduces corneal staining in their patients [78]. In a study of corneal nerve structure and function in 20 patients fitted with a fluid filled scleral lens, patients with a distorted cornea had significantly reduced basal tear production and increased corneal sensation after long-term wear of the scleral lens, whereas patients with ocular surface disease did not show any changes in tear production or corneal sensation [79].…”
Section: Scleral Lensesmentioning
confidence: 99%
“…111 A more recent study, however, indicated that long-term PROSE wear did not result in increased corneal nerve density by IVCM. 112 Nevertheless, while some patients with NCP may experience immediate pain relief, using CLs may be challenging in NCP patients with severe underlying hyperalgesia, in whom lenses can provide strong noxious stimuli.…”
Section: Management Of Patients With Neuropathic Corneal Painmentioning
confidence: 99%
“…The maximum analgesic dose of gabapentin recommended for adults is usually between 1,800 and 3,600 mg per day. 112 Pregabalin is started at a dose of 75 mg at bedtime, with a gradual weekly increase to a maximum of 600 mg daily. While the authors have had similar success in patients with ocular PHN, the response rate in patients with NCP of other origins has been very limited.…”
Section: Management Of Patients With Neuropathic Corneal Painmentioning
confidence: 99%